ISOLATED INFERIOR OBLIQUE MYECTOMY FOR HYPERTROPIA - Bukhari, Sadia; Kazi, Ghulam Qadir; Qidwai, Umair (Journal of Ayub Medical College Abbottabad, 2014)
Background: Hypertropia is a condition in which one eye is elevated relative to the other, either intermittently or constantly. It causes significant problem either cosmetically or by abnormal head posture and thus needs to be corrected surgically. This study was conducted to evaluate the success rate and complications of isolated inferior oblique myectomy in patients with hypertropia. Methods: Patients having hypertropia (Deviation >6 prism diopters [PD]) associated with inferior oblique over-action were included in this observational Case-series, conducted from July 2011 to December 2012, at Al Ibrahim eye Hospital, Karachi. Patients underwent unilateral inferior oblique myectomy. Final outcome was considered at the end of three months at which achievement of ‰¤2 PD of hypertropia was considered as a success. Results: During the study period, 58 patients were included. Hypertropia was most commonly associated with exotropias 23 (39.7%) followed by esotropias in 18 (31%). Mean angle of hypertropia was reduced from 13.55±4.43 prism diopters to 0.48±1.08 prism diopters. Out of 58 patients, 55 (94.8%) had achieved success after surgery while only 3(5.2%) patients had residual hypertropia of greater than 2 prism diopters (p=0.001). No direct complications of procedure observed intra-operatively or up to 3 months post operatively but significant overcorrection of residual horizontal deviation observed after horizontal squint surgery in these eyes. Conclusion: Isolated inferior oblique myectomy is highly successful and safe surgical procedure for correction of hypertropia. Keywords: Hypertropia, Inferior oblique myectomy, outcome